Sustaining international graduate education: Policy pressures, institutional leadership, and student lived experience in Canada - Mohamed, Derrick Rasheed; George, Imbenzi (Journal of International Students, 2026)
International graduate education in Canada is increasingly shaped by shifting immigration policies, rising living costs, and institutional sustainability pressures. While policy discussions emphasize enrollment and financial models, less attention has been given to students’ lived experiences. This study examines how financial pressure, policy uncertainty, academic expectations, and institutional systems intersect in the experiences of 525 international graduate students. Using a convergent parallel mixed methods design, quantitative and qualitative data were collected concurrently, analyzed independently, and integrated. The findings reveal that sustainability is experienced as a cumulative and relational condition shaped by financial precarity, immigration uncertainty, academic adjustment, social belonging, and trust in institutional support. The study extends adaptive leadership frameworks within immigration-constrained contexts and positions academic hospitality as a mediating leadership practice. It proposes a relational-policy leadership lens linking policy environments, institutional decision-making, and student experience, offering implications for leadership in complex international education systems.